Automatic Identification Algorithm for Semantic Relations of Chinese Natural Language Entities - Xinle, Chen (2022 International Conference on Knowledge Engineering and Communication Systems (ICKES), 2022)
Semantic parsing, in a sense, is a formal language process that translates natural language into computer recognizable language. Therefore, semantic parsing can be treated as a special machine translation problem. Modern Chinese semantic research oriented to natural language processing, on the one hand, can deepen our understanding of the nature and characteristics of Chinese, on the other hand, can provide valuable semantic resources for computer processing of Chinese. This research strives to make breakthroughs in both theory and practice. Based on the principle of serving natural language processing, it constructs a Chinese sentence semantic knowledge system, and on this basis, it conducts theoretical research and practical exploration on the construction of Chinese sentence semantic knowledge base, which can not only provide a useful knowledge system for Chinese information processing, but also provide a reference for the construction of large-scale Chinese sentence semantic knowledge base in the next stage.